Through our eyes : an action research project exploring the identities and experiences of NEETs in a South African township - Haynes-Rolando, Hayley (My University, 2016)
The study sought to give voice to the subjective experiences of NEETs (youth not in employment, education or training), often viewed as risk taking, apathetic and a strain on the economy and to think about their identities differently. The aim was also to provide ways to forge new versions of themselves in the future, allowing the participants an opportunity to ‘read the world’ differently and to think about new possibilities, through recollecting the past and exploring their present place in the world. This study utilised participatory action research and narrative inquiry to explore the experiences of a group of NEETs in a township in South Africa, and together with the researcher were involved in active engagement with their social worlds, through photographic documentation and in-depth interviews. The data were analysed using thematic and narrative analysis. The focus of the narrative analysis was to understand the meaning that the participants made of their own experiences, and the thematic and visual analysis focussed on understanding their context, their interaction with place and people in forming their identities, and the opportunities and versions of identities that they thought were possible in the future. The significance of these findings points to the past and the effects of South Africa’s history on youth identity. However, despite the structural constraints that impact on youth growing up in disadvantaged townships, and the impact that these constraints have on their identities, these youth have found ways to challenge the stereotypes that define their lives, and in different ways offer glimmers of hope for their futures. Their identities, though impacted by their interaction with their environment and the people in their context, are remarkably complex and encouraging. Furthermore, this study provided insight into the issues facing ‘at risk’ youth, and allows for new possibilities for their issues and concerns to be addressed.
Masters thesis submitted to the Faculty of Humanities School of Human and Community Development Discipline of psychology for the degree of Master in Educational Psychology University of the Witwatersrand, Johannesburg, 2016
Keywords: Youth, Black--South Africa--Psychology; Youth, Black--South Africa--Social conditions; Youth--Employment--South Africa; Group identity--South Africa